PERFORMANS PRODUKSI BURUNG PUYUH BETINA (Coturnix coturnix japonica) PADA LAMA PENCAHAYAAN YANG BERBEDA - Rotikan, Febrian; Lambey, L.J.; Bagau, B.; Laihat, J. (ZOOTEC, 2018)
PRODUCTION PERFORMANCE OF FEMALE QUAILS (Coturnix coturnix japonica) UNDER DIFFERENT LIGTH ILLUMINATIONS. The objective of this study was to evaluate the duration effect of light illuminations on egg production performance of female quails (Coturnix coturnix japonica). Total of 80 female quails at the age of 3 weeks old were used in this study. The total of 4 birds were raised in the cage of 40x30 cm. Birds were randomly put in the cage using completely randomized design for the four treatments consisting of cage without light illumination (R0), cage with light illumination during 4 hours per day (R1), cage with light illumination during 8 hours per day (R2), and cage with light illumination during 12 hours per day (R3). Variables measured were feed consumption, age at first laying egg, egg production and egg weight. Results showed that light illumination did not significantly affect feed consumption, age at first laying egg, egg production and egg weight. Therefore, it can be concluded that production management of female quails (Coturnix coturnix japonica) did not need light illumination during 4, 8 and 12 hours per day.Â Key words: Female quail, Light illuminations, Production performance